2014
DOI: 10.1016/j.jaci.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Emollient enhancement of the skin barrier from birth offers effective atopic dermatitis prevention

Abstract: BackgroundAtopic dermatitis (atopic eczema) is a chronic inflammatory skin disease that has reached epidemic proportions in children worldwide and is increasing in prevalence. Because of the significant socioeconomic effect of atopic dermatitis and its effect on the quality of life of children and families, there have been decades of research focused on disease prevention, with limited success. Recent advances in cutaneous biology suggest skin barrier defects might be key initiators of atopic dermatitis and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
507
3
39

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 644 publications
(559 citation statements)
references
References 31 publications
10
507
3
39
Order By: Relevance
“…Recent insights indicate that the primary abnormality in eczema is a skin barrier defect. Allergic sensitization is a secondary phenomenon which increases the severity and longevity of atopic disorders 28. Thus, interventions that reduce sensitization and/or induce tolerance may be more important for long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent insights indicate that the primary abnormality in eczema is a skin barrier defect. Allergic sensitization is a secondary phenomenon which increases the severity and longevity of atopic disorders 28. Thus, interventions that reduce sensitization and/or induce tolerance may be more important for long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed that the daily use of emollients prevents AD or reduces flare-ups (45,46). Recently, an expert panel reached consensus that the use of appropriate emollients at all post-inflammatory AD stages has the potential to maintain skin hydration with reduced acute exacerbations of AD (1).…”
Section: Dryness Body Facementioning
confidence: 99%
“…16 Building on this observation, recent clinical trials have produced evidence to suggest that intensive emollient use from soon after birth, aimed to enhance the skin barrier, reduces the incidence of eczema by ∼50% in high-risk infants (defined as those with a first-degree relative having atopic disease). 17 However, the authors emphasise that larger trials are required before this approach can be recommended for routine clinical practice.…”
Section: Advances In Understanding the Aetiology And Pathogenesis Ofmentioning
confidence: 99%